Restraint of trade at common law - Dempster, Hamish Leslie (University of Auckland, 1997)
This is a collection of essays about the restraint of trade doctrine as laid down in the courts of the United Kingdom and the British Commonwealth. Generally, I will not give an account of the restraint of trade doctrine in the United States of America, for even although each individual state (apart from the civil jurisdictions California and Louisiana) and the federation itself, has a common law system, for reasons peculiar to those jurisdictions, the restraint of trade case law there has become so vast and so confused as to be unsuitable for my purposes. More importantly, however, the common law restraint of trade doctrine in the United Kingdom and the British Commonwealth has been laid down by courts without any significant consideration of the state of the law in the United States. Davies v Davies (1887) 36 Ch D 359, 370 by contrast, the period during which the Privy Council operated as a supra national court of final appeal has resulted in considerable harmony in the doctrine within the British Commonwealth. Even now the House of Lords is influential in Australia and Canada and the influence is increasingly reciprocal. By way of an exception I will discuss the purposes of the anti-trust legislation in the United States. This is necessary because I intend to show that the common law restraint of trade doctrine was not able to be, and was never intended to be, a means of regulating the economy in contradistinction to the United States anti-trust legislation and related legislation in the British Commonwealth. This account is not merely a description of the law relating to the restraint of trade doctrine although I do purport to describe the law. There are other accounts of the restraint of trade doctrine which do that well. Accounts of the restraint of trade doctrine include: Matthews & Adler, The Law Relating to Covenants in Restraints of Trade (London, 2nd ed 1907); Sanderson, Restraint of Trade in English law (London, 1926); Heydon, The Restraint of Trade Doctrine (London, 1971); Trebilcock, The Common Law of Restraint of Trade; A Legal and Economic Analysis (Toronto, 1986); Dean, The Law of Trade Secrets (Sydney, 1990); Mehigan & Griffiths, Restraint of Trade and Business Secrets: Law & Practice (London, 2nd ed 1991); Holdsworth, History of English Law IV (3rd ed, 1945) 343-54, 373-9; VIII (2nd ed, 1937) 56-42. There are other, less detailed accounts in contract law textbooks. The purpose of this dissertation is to describe aspects of the doctrine as it developed between the medieval period and the twentieth century and then to use that account as a basis for an analysis of how the law has taken a number of paths during the twentieth century which cannot be justified by the rules and their justifications which existed in the law prior to that time. Such a development has had important consequences for the restraint of trade doctrine and even the law in general, most of which have been detrimental. I do not intend to give a continuous historical narrative covering the whole of the doctrine. The history has been described before. For example, I do not intend to give a discrete account of the process by which the absolute rule against general restraints of trade gave way to the rule of reason, although I do mention this process where relevant for other purposes. The history, so far as it is relevant, is integrated into each chapter. I will argue that historically the restraint of trade doctrine was a rule or complex of rules, of a certain form and content. The form and content of the rule are important because they bear on the meaning of the class term "restraint of trade" which is an element of the rule. The meaning of that term began to change around the year 1890. Beginning first with certain classes of trade combination, courts began to classify as restraints of trade covenants which did not in fact restrain trade. Then the courts similarly treated the exclusive dealing contract and certain forms of property transaction. Another trend in the law which added to the confusion about the meaning of restraint of trade was the failure by the courts to make definitive findings one way or another as to whether a particular covenant was in restraint of trade. The courts were then faced with a dilemma. The law required a court to refuse to enforce a covenant in restraint of trade unless the covenantee could justify the restraint by presenting evidence to the court from which the courts could assess whether or not that particular restraint was within the reason for the restraint of trade doctrine or not. Such considerations were entirely inapt in the case of covenants which, in accordance with the traditional view, did not restrain trade. Yet if the courts did not validate these contracts, catastrophic consequences would have followed for the parties to such contracts and, indeed, to contract as an institution. To solve the dilemma the courts began to interpret the famous statement of the restraint of trade doctrine by Lord Macnaghten in Nordenfelt v Maxim Nordenfelt Guns & Ammunition Co [1894] AC 535, 565 (HL) literally, rather than contextually. Ultimately this has resulted in the obscuring of the rule underlying the restraint of trade doctrine itself. There were many minor confusions along the way. It is important that the doctrine is coherent and its use consistent with its justifications because it is still a fruitful cause of legal change. In the last year the force of the rule has caused a radical restructuring of Association Football in Europe Bosman’s case. The rule has even penetrated the collective consciousness of the community at large. The broad thrust of the development and the detail will be outlined in the next thirteen chapters.

A behavioural study of the rental housing market in Ibadan, Oyo State of Nigeria - Asaju, Adebakin Simeon (Obafemi Awolowo University, 1994)
Keywords: Besoins en logement; Composition du ménage; Household composition; Housing market; Housing needs; Ibadan; Logement locatif; Marché du logement; Nigeria; Oyo State; Rental housing; État d'Oyo

Trade and justice - Robe, Jean-Philippe (European University Institute, 1992)
Keywords: Intergovernmental fiscal relations; Justice; Trade